Socio‐eco‐evolutionary dynamics in cities. (19th August 2020) - Des Roches, Simone; Brans, Kristien I.; Lambert, Max R.; Rivkin, L. Ruth; Savage, Amy Marie; Schell, Christopher J.; Correa, Cristian; De Meester, Luc; Diamond, Sarah E.; Grimm, Nancy B.; Harris, Nyeema C.; Govaert, Lynn; et al.
Abstract: Cities are uniquely complex systems regulated by interactions and feedbacks between nature and human society. Characteristics of human society—including culture, economics, technology and politics—underlie social patterns and activity, creating a heterogeneous environment that can influence and be influenced by both ecological and evolutionary processes. Increasing research on urban ecology and evolutionary biology has coincided with growing interest in eco‐evolutionary dynamics, which encompasses the interactions and reciprocal feedbacks between evolution and ecology. Research on both urban evolutionary biology and eco‐evolutionary dynamics frequently focuses on contemporary evolution of species that have potentially substantial ecological—and even social—significance. Still, little work fully integrates urban evolutionary biology and eco‐evolutionary dynamics, and rarely do researchers in either of these fields fully consider the role of human social patterns and processes. Because cities are fundamentally regulated by human activities, are inherently interconnected and are frequently undergoing social and economic transformation, they represent an opportunity for ecologists and evolutionary biologists to study urban "socio‐eco‐evolutionary dynamics." Through this new framework, we encourage researchers of urban ecology and evolution to fully integrate human social drivers and feedbacks to increase understanding and conservation of ecosystems, their functions and their contributions to people within and outside cities.